The Effect of Financial Distress, Audit Opinion and Audit Fee on Auditor Switching (Empirical Study on Mining Companies Listed on the Indonesia Stock Exchange) - Lewier, Imanuella Gizkha; Usmany, Paul; Loupatty, Linda Grace (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to analyze the effect of financial distress, audit opinion, and audit fee on auditor switching in mining companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative research method. The sampling technique in this study uses a purposive sampling technique. The population is all mining sector companies listed on the IDX in 2022-2023, totaling 85 companies and the research sample is 46 companies. Using logistic regression analysis with SPSS 25.0 software in analyzing data in the preparation of this study. The results of this study are that financial distress and audit opinion do not have a significant effect on the company's decision to conduct auditor switching. Meanwhile, audit fees have a significant effect on the company's decision to conduct auditor switching.